2012
DOI: 10.1128/aem.07990-11
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Quantification of Clostridium difficile Cells by Reverse Transcription-Quantitative PCR Targeting rRNA Molecules

Abstract: ABSTRACTWe established a sensitive and accurate quantification system forClostridium difficilein human intestines, based on rRNA-targeted reverse transcription-quantitative PCR (RT-qPCR). We newly developed a species-specific primer set forC. difficiletargeting 23S rRNA gene sequences. Both the vegetative cells and the spores of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 56 publications
(67 reference statements)
1
45
0
Order By: Relevance
“…After incubation at room temperature for 10 min, the fecal samples were cooled to -20 ° C and then mailed to the Yakult Central Institute. The bacterial counts were determined using the Yakult Intestinal Flora-SCAN (YIF-SCAN) according to the RT quantitative PCR technique [13,14]. The specificity of the RTquantitative PCR assay group-, species-, the Staphylococcus spa gene, and the Staphylococcus mecA gene-specific primers was determined as described previously [15] .…”
Section: The Pre-specified Secondary Outcome: the Intestinal Microbiomentioning
confidence: 99%
“…After incubation at room temperature for 10 min, the fecal samples were cooled to -20 ° C and then mailed to the Yakult Central Institute. The bacterial counts were determined using the Yakult Intestinal Flora-SCAN (YIF-SCAN) according to the RT quantitative PCR technique [13,14]. The specificity of the RTquantitative PCR assay group-, species-, the Staphylococcus spa gene, and the Staphylococcus mecA gene-specific primers was determined as described previously [15] .…”
Section: The Pre-specified Secondary Outcome: the Intestinal Microbiomentioning
confidence: 99%
“…We theorize that in order to better assess the impact of fecal pollution it is important to target active cells via rRNA-based detection of gene markers in fecal source tracking studies. Since metabolically active cells usually contain higher numbers of ribosomes than quiescent cells (26), it is not a surprise that recent studies have shown that rRNA-targeted RT-qPCR assays can be more sensitive than rRNA gene-based qPCR assays (27,28). In addition, the rRNA/rRNA gene ratio from each target bacterium is an important indicator of its metabolic status within bacterial communities and has been used to provide an estimate of in situ bacterial growth rates (29,30).…”
mentioning
confidence: 99%
“…Furthermore, while DNA-based PCR detects both viable and dead microorganisms, YIF-SCAN quantifies viable microorganisms, because rRNA molecules are better indicators of the status of viable microorganisms than rRNA genes [11] . Also, the data obtained by YIF-SCAN are almost equivalent to those obtained by fluorescence in situ hybridization targeting rRNA molecules [9,10,[12][13][14][15] .…”
Section: Principle Of Yif-scanmentioning
confidence: 90%
“…Focusing on the possibility of using YIF-SCAN to improve the accuracy of the diagnosis of pathogenic microorganisms, we developed primer sets not only for indigenous intestinal bacteria [11,12,15,17,[39][40][41][42] , but also for various pathogenic microorganisms that can be detected in clinical settings ( Table 1 ). Along with the intestinal bacterial analysis, we have also developed a highly sensitive system for quantifying Streptococcus such as Streptococcus pyogenes , S. agalactiae , and S. pneumoniae/ mitis (frequently detected in sepsis) [43] ; Clostridium difficile (pathogenic bacterium of antibiotic-induced diarrhea) [13] ; Candida albicans , C. glabrata , C. tropicalis , C. parapsilosis , and C. krusei (pathogenic fungi of mycoses) [44] ; Vibrio cholerae/mimicus , V. parahaemolyticus/alginolyticus , and Campylobacter jejuni/coli (pathogenic bacteria of food poisoning) [16] ; Lactobacillus crispatus , L. gasseri , L. jensenii , and L. iners (indigenous vaginal bacteria); Atopobium vaginae , Gardnerella vaginalis , and Mobiluncus curtisii (pathogens of bacterial vaginosis), Mobiluncus curtisii , and Chlamydia trachomatis/muridarum (pathogenic bacteria of sexually transmitted disease) [45] .…”
Section: Detection Of Bacteria In Blood By Yif-scanmentioning
confidence: 99%